Challenges of information security laws and legislations in Nigeria’s institutions of higher education: Views from Yola, Adamawa state - Ngboawaji Daniel Nte; Vigo Augustine Teru; Arifin Ridwan (Universitas Muhammadiyah Malang, 2024)
The menace of threats against information security worldwide cannot be overemphasis. The whole gamut of statecraft, national security, public safety, international trade and indeed postmodernity revolves around information security. As a country, Nigeria is part of a global system facing this monumental threat and institutions of higher education are a subset of the vulnerability circle. This work therefore seeks to evaluate the challenges of implementation of information security laws and legislations in Nigerian institutions of higher education with special focus of higher education institutions in Yola, Adamawa State. Generally, the work investigated the impact of information security threats and attacks in institutions of higher learning, the role of security laws and legislations in combating these threats, the challenges of information security threats management and indeed possible solutions to these challenges. The work utilised a qualitative research method through the application of archival and documentary research, and Case study research (multiple case study) and interviews from a selected sample. Consequently, the study was able to evaluate the state of awareness of information security in this sector, the implementation challenges of the existing information security laws and regulations and offered valuable policy recommendations to the various stakeholders on how to implement sustainable information security laws and legislations to guarantee the protection of critical data assets not just in institutions of higher education in Nigeria but the entire country and in tandem with global best practice.